The physiologic anticoagulant and anti-inflammatory role of heparins and their utility in the prevention of pregnancy complications - Mastrolia, Salvatore Andrea; Mazor, Moshe; Holcberg, Gershon; Leron, Elad; Beharier, Ofer; Loverro, Giuseppe; Erez, Offer (Thrombosis and Haemostasis, 2015)
Accumulating evidence supports the concept of increased thrombin generation, placental vascular lesions, and inflammation as crucial points in the development of the great obstetrical syndromes [preeclampsia, intrauterine growth restriction (IUGR), preterm labor (PTL), preterm prelabor rupture of membranes (PROM), fetal demise and recurrent abortions]. In light of this, the role of heparins for primary or secondary prevention of these syndromes is becoming more and more apparent, mainly due to the antithrombotic and anti-inflammatory effects of heparins. There is agreement regarding the use of heparin in the prevention of gestational complications in patients with antiphospholipid syndrome, while its use for other obstetrical complications is under debate. In the present review we will describe the physiologic role of heparins on coagulation and inflammation and we will discuss current evidence regarding the use of heparins for the prevention/ treatment of obstetrical syndromes.
Keywords: Antiphospholipid syndrome; inflammation; preterm labour; recurrent pregnancy loss; thrombin generation